2021
DOI: 10.2147/ott.s313669
|View full text |Cite
|
Sign up to set email alerts
|

Testing for EGFR Mutations and ALK Rearrangements in Advanced Non-Small-Cell Lung Cancer: Considerations for Countries in Emerging Markets

Abstract: The treatment of patients with advanced non-small-cell lung cancer (NSCLC) in recent years has been increasingly guided by biomarker testing. Testing has centered on driver genetic alterations involving the epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) rearrangements. The presence of these mutations is predictive of response to targeted therapies such as EGFR tyrosine kinase inhibitors (TKIs) and ALK TKIs. However, there are substantial challenges for the implementation of biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 181 publications
(296 reference statements)
0
7
0
1
Order By: Relevance
“…Advancements in pathophysiological understanding have increased the array of treatment options for local and advanced disease, leading to individual treatment plans. Advancements in pathophysiological understanding of molecular targeted therapy and immunotherapy (5), such as epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK), have improved the prognosis of LUAD patients (21), while a considerable number of LUAD still lack specific targets. Previous studies have shown that LDH-C4, as an important tumor CTA, plays an important role in tumorigenesis and development (10)(11)(12)(13)(14)(15)19), acting as a potential target for tumor immunotherapy (22).…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in pathophysiological understanding have increased the array of treatment options for local and advanced disease, leading to individual treatment plans. Advancements in pathophysiological understanding of molecular targeted therapy and immunotherapy (5), such as epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK), have improved the prognosis of LUAD patients (21), while a considerable number of LUAD still lack specific targets. Previous studies have shown that LDH-C4, as an important tumor CTA, plays an important role in tumorigenesis and development (10)(11)(12)(13)(14)(15)19), acting as a potential target for tumor immunotherapy (22).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used tissue assays that are currently available to identify ALK fusions include both traditional single methodologies such as immunohistochemistry (IHC), break-apart fluorescence in situ hybridization (FISH) and real-time PCR, as well as the increasingly popular NGS ( 42 - 51 ). Each of these approaches has advantages and disadvantages that need to be carefully balanced to design sensible testing algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted NGS Panels are helpful for finding different mutations, such as T790M, and are capable of sequencing numerous genes at once. They are useful for comprehending the larger genetic profile of a patient's tumor of their great sensitivity and comprehensiveness [18].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…On the other hand, T790M and other gene amplifications and mutations can be found in tissue samples using EGFR T790M FISH Probes. Fluorescently labeled probes that bind to particular DNA sequences are used in FISH [18].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%